Design of small hand-launched solar-powered UAVs: From concept study to a multi-day world endurance record flight - Oettershagen,P; Melzer,A; Mantel,T; Rudin,K; Stastny,TJ; Wawrzacz,B; Hinzmann,T; Leutenegger,S; Alexis,K; Siegwart,R (Journal of Field Robotics, 2017)
We present the development process behind AtlantikSolar, a small 6.9 kg hand-launchable low-altitude solar-powered unmanned aerial vehicle (UAV) that recently completed an 81-hour continuous flight and thereby established a new flight endurance world record for all aircraft below 50 kg mass. The goal of our work is to increase the usability of such solar-powered robotic aircraft by maximizing their perpetual flight robustness to meteorological deteriorations such as clouds or winds. We present energetic system models and a design methodology, implement them in our publicly available conceptual design framework for perpetual flight-capable solar-powered UAVs, and finally apply the framework to the AtlantikSolar UAV. We present the detailed AtlantikSolar characteristics as a practical design example. Airframe, avionics, hardware, state estimation, and control method development for autonomous flight operations are described. Flight data are used to validate the conceptual design framework. Flight results from the continuous 81-hour and 2,338 km covered ground distance flight show that AtlantikSolar achieves 39% minimum state-of-charge, 6.8 h excess time and 6.2 h charge margin. These performance metrics are a significant improvement over previous solar-powered UAVs. A performance outlook shows that AtlantikSolar allows perpetual flight in a 6-month window around June 21 at mid-European latitudes, and that multi-day flights with small optical- or infrared-camera payloads are possible for the first time. The demonstrated performance represents the current state-of-the-art in solar-powered low-altitude perpetual flight performance. We conclude with lessons learned from the three-year AtlantikSolar UAV development process and with a sensitivity analysis that identifies the most promising technological areas for future solar-powered UAV performance improvements.